Wetland birds of middle Vistula River during breeding season: the impact of human activities on the distribution, abundance and richness of species - Bukaciński, Dariusz; Bukacińska, Monika; Buczyński, Arkadiusz (Studia Ecologiae et Bioethicae, 2020)
The inventory of birds was conducted in the years 2005-2010 on the Vistula River section between Dęblin (km 388 of the river) and Podwierzbie (km 435 of the river). The study area includes a southern section of the European Ecological Natura 2000 Site in Poland PLB140004 "Middle Vistula River Valley” (IBA, PL083). On most areas the Vistula flows here within unregulated or relatively little modified riverbed, having features of a natural, lowland, braided river. Sandy islands and braid bars within a main channel, steep banks and old riparian afforestation create the unique breeding habitats of the Vistula River Valley. Especially the river channel habitats provide suitable breeding sites for many rare bird species, constituting for some of them the key-breeding sites. There are, however, fragments of several kilometres, where people transformed the Vistula River in a more noticeable way (Table 1). These are, among others: an urban section within Dęblin boundaries (km 388 to km 393 of the river), a fragment adjacent to Kozienice Power Plant (km 421 to km 426) and the area, where since 2007 gravel for industry has been mined from the river bottom (km 426 to km 431). The aim of this inventory was the comparison of richness and abundance of breeding bird species linked directly to the river channel in fragments mentioned above. It will allow to estimate soberly how very the intensity of human utilization of the river affects the distribution of avifauna of the Vistula, determining the richness and abundance of valuable and/or endangered species breeding in a given area. In the years 2007-2009 within a whole study area 32 breeding species characteristic for the riverbed and its surroundings were recorded. Among them 6 are threatened in Poland: mew gull (Larus canus), little tern (Sternula albifrons), ringed plover (Charadrius hiaticula), Eurasian oystercatcher (Haematopus ostralegus), corncrake (Crex crex) and hoopoe (Upupa epops) (Table 2a, b). The comparison of bird richness revealed significant differences between adjoining fragments of the river (Table 3). Decidedly the most valuable was the section between Wróble and Kozienice Power Plant (km 416-421). The Vistula River flows here within a riverbed only a little changed by man. It has an appearance typical for a large, lowland braided river with meandering channels, network of small side channels, steep banks, sandy bars and different kind of islands. Such differentiated environment is reflected in richness of birds. The association of 27-30 species reached here the total density of 337-397 pairs/km along the river, unparalleled in other habitats (Table 3). The urban section within Dęblin boundaries (km 388-393) and a 5-kilometer-long area of gravel mining (km 426-431) were much less attractive for birds. Straight, much narrower river channel, small number of islands in a main channel and a degraded valley in the vicinity of river banks caused, that only six to ten species nested there, of the total density ranged between 2.0-2.7 pairs/km on the urban fragment and 3.8-6.6 pairs/km within the gravel pit area (Table 3). However, these values are quite high in comparison to those recorded for the fragment adjoining Kozienice Power Plant (km 421-426). The river channel is here clearly contracted and the bottom is deepened. The river flows fast within one channel. Numerous, concrete, submerged groynes, revetments on both sides of the river and a bank made of concrete, protecting a power station are very characteristic for this place. Such a man-made environment almost excludes the possibility of breeding of birds within a riverbed. Only single pairs of lapwings (Vanellus vanellus), common sandpipers (Actitis hypoleucos), little ringed plovers (Charadrius dubius) and goosanders (Mergus merganser) occurred here, sporadically also common terns (Sterna hirundo) (Table 2a,b). The total density was very low and did not exceed 1.5 pairs/km along the river. The yearly surveys of birds in the years previous to and after beginning of a gravel and sand mining from the river bottom allowed to estimate if the development had changed somehow the status of riparian bird populations. During three years of an activity a negative impact of the development on the richness and abundance of bird species was not recorded, both in direct vicinity and on the fragment below (Table 4). Not the small harmfulness of the development finally influences the status and changes of avifauna in these sections, but the place where it is situated. It should be kept in mind that the sand mining takes place only within 2 km of the section of Vistula that is regulated to a large degree, and the section above is almost unavailable for riparian birds (Kozienice Power Station). One can assume with high probability bordering on certainty that when the gravel excavation took place on the fragment between km 393 and km 421 or below km 431 of the river, the negative impact of the development on breeding habitats and avifauna of the river channel would be much more noticeable and worse still – it would be irreversible. Both fragments mentioned above are now unique places, where the bird association characteristic for the unregulated channel of lowland river can be found – the environment, which irrevocably declines due to human activities.